2010
DOI: 10.5194/bg-7-315-2010
|View full text |Cite
|
Sign up to set email alerts
|

Responses of soil respiration to elevated carbon dioxide and nitrogen addition in young subtropical forest ecosystems in China

Abstract: Abstract. Global climate change in the real world always exhibits simultaneous changes in multiple factors. Prediction of ecosystem responses to multi-factor global changes in a future world strongly relies on our understanding of their interactions. However, it is still unclear how nitrogen (N) deposition and elevated atmospheric carbon dioxide concentration [CO 2 ] would interactively influence forest floor soil respiration in subtropical China. We assessed the main and interactive effects of elevated [CO 2 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(69 citation statements)
references
References 71 publications
4
65
0
Order By: Relevance
“…Litterfall is supplied for heterotrophic microbe respiration (Reichstein et al, 2002;Zhou et al, 2013). These processes are influenced by soil nitrogen content (Allison et al, 2008;Deng et al, 2010). These findings support our first hypothesis that topographic heterogeneity in R s was controlled by the respiration substrate supply provided by plants.…”
Section: Plant Drivers Of the Topographic Variation In Soil Respiratisupporting
confidence: 78%
“…Litterfall is supplied for heterotrophic microbe respiration (Reichstein et al, 2002;Zhou et al, 2013). These processes are influenced by soil nitrogen content (Allison et al, 2008;Deng et al, 2010). These findings support our first hypothesis that topographic heterogeneity in R s was controlled by the respiration substrate supply provided by plants.…”
Section: Plant Drivers Of the Topographic Variation In Soil Respiratisupporting
confidence: 78%
“…Yet, some studies also report closed stomata in herbaceous plants and tree seedlings even when there was ample soil moisture, if the air was considerably dry and VPD consequently elevated (Leuschner, 2002;Lendzion & Leuschner, 2008;Kupper et al, 2011). Stomatal control and therefore photosynthetic efficiency are also influenced by levels of CO 2 in the air (Kramer & Boyer 1995), which is additionally released from the forest floor by decomposition processes and root respiration (Neufeld & Young 2003), particularly when soils are moist and warm (Deng et al 2010;Lloyd & Taylor 1994;Raich & Tufekciogul 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The production of CO 2 in soils is almost entirely from root respiration and microbial decomposition of organic C. Like all chemical and biochemical reactions, these processes are subject to soil temperature and water limitation [12]. In this study, we found that the release rate of CO 2 from soil was controlled by both soil temperature and soil moisture, and that 30˚C soil temperature seems to be a threshold of soil temperature (Figure 3).…”
Section: Soil Co 2 Flux Under Different Fertilizer and Soil Managementmentioning
confidence: 62%
“…Increase of crop growth that may result in high yield may also increase soil CO 2 flux from croplands, and as a result may weaken the potential of soil C sequestration [8] [9]. Soil CO 2 flux involves complex biological processes that are controlled by many environmental factors such as soil temperature and soil moisture [10]- [12]. Shifts of soil properties or microclimate following agricultural practices may influence CO 2 flux [13]- [15].…”
Section: Introductionmentioning
confidence: 99%